"I'm Literally Drowning": A Mixed-Methods Exploration of Infant-Toddler Child Care Providers' Wellbeing. Issue 7 (2nd October 2020) - Berlin, Lisa J.; Shdaimah, Corey S.; Goodman, Alyssa; Slopen, Natalie
ABSTRACT: Research Findings: The primary goal of this exploratory mixed-methods study was to obtain a deeper understanding of center-based child care providers serving infants and toddlers. Secondarily, we explored the potential for a two-pronged mindfulness-based caregiving intervention for such providers to (a) reduce stress and (b) support caregiving behaviors. We conducted (a) individual interviews with three child care center directors and (b) three center-specific focus groups in order to elicit background information on each center and its staff, providers' views of work benefits and challenges, and both providers' and center directors' initial receptivity to a mindfulness-based caregiving intervention. Additionally, 23 infant-toddler providers from the same three centers completed an anonymous questionnaire that assessed demographic and socioeconomic characteristics, social and emotional well-being, physical health, and perceived job characteristics. Findings illustrate high levels of physical and mental health problems. Practice and Policy : Findings provide some insight into aspects of the work that may serve as stressors (e.g., low pay, responding to children's challenging behaviors) and buffers (e.g., supportive relationships with coworkers and supervisors). Findings also illustrate center directors' and providers' receptivity to a mindfulness-based caregiving intervention.